The relationship between personality and psychological level Achievement of the players lifting weights - Jassim Abbas, Moayad (Journal of Physical Education, 2012)
Psychological factor plays an important and effective role alongside technical and physical factor, and one of the phenomena that concern directly affects human behavior, emotion and motor private players lifting weights. The importance of this research lies in identifying the type and level of concern and its impact on the level of achievement of the players lifting weights, as the research aims to identify the degree of anxiety and fear among sports players lifting weights, as well as to identify mathematical relationship anxiety and fear of accomplishment. The researcher concluded that there is a significant correlation between fear and sports achievement and anxiety and achievement, between fear and anxiety sports, the study also showed the presence of a significant correlation between the anxiety scale sports and disabilities and anxiety facilitator. The researcher recommends that attention by the trainers to know the levels of anxiety that accompany lifters during races and direct way that helps in achieving the feat weightlifter, also recommends training lifters during daily training modules on how to invest fear and anxiety associated with athletic performance.